Covenant in the Persian Period - Steven Schweitzer; Thomas B. Dozeman; Sean Burt; Melody D. Knowles; Thomas Römer; Richard J. Bautch; Gary N. Knoppers (Journal of Hebrew Scriptures, 2018)
The recent publication, Covenant in the Persian Period: From Genesis to Chronicles, edited by Richard J. Bautch and Gary N. Knoppers (Eisenbrauns, 2015), contains 22 essays on the topic of covenant within various Hebrew Bible texts. The six articles published here reflect interactions in a review session of the SBL Chronicles–Ezra–Nehemiah Section in November 2016. The essays were distributed among four reviewers (Thomas Dozeman, Sean Burt, Melody Knowles, and Thomas Römer). The two editors offered responses. The scope of this engagement enhances the value of the volume for those working on covenant and on these texts.